Pseudotumour in a Haemophiliac with Inhibitor - Vasanthiamma Krishnannair Sreekala; Anila Das Greeshma (Indian Journal of Physical Medicine & Rehabilitation)
A 41-year-old male haemophilic patient with inhibitor developed recurrent bleeding in the right thigh and eventually developed pseudotumour. Pseudotumour gradually progressed and ruptured on the evening of elective surgery. He had undergone excision of pseudotumour at Christian Medical College, Vellore. Post-operative period was uneventful. He was managed with factor eight inhibitor bypass agents. Now, he is ambulant with an assistive device.